Outcomes following restrictive or liberal red blood cell transfusion in patients with lower gastrointestinal bleeding. Issue 7 (25th February 2019) - Kherad, Omar; Restellini, Sophie; Martel, Myriam; Sey, Michael; Murphy, Michael F.; Oakland, Kathryn; Barkun, Alan; Jairath, Vipul
Summary: Background: Restrictive red blood cell (RBC) transfusion reduces mortality and rebleeding after upper gastrointestinal bleeding (UGIB). However, there is no evidence to guide transfusion strategies in lower gastrointestinal bleeding (LGIB). Aim: To assess the association between RBC transfusion strategies and outcomes in patients with LGIB Methods: This was a post hoc analysis of the UK National Comparative Audit of LGIB and the Use of Blood. The relationships between liberal RBC transfusion and clinical outcomes of rebleeding, mortality and a composite outcome for safe discharge were examined. Transfusion strategy was dichotomised and defined as "liberal" when transfusion was administered for haemoglobin (Hb) ≥80 g/L (or ≥90 g/L in patients with acute coronary syndrome) or major haemorrhage, and "restrictive" otherwise. Multivariable logistic regression models were used to assess the independent association between liberal RBC transfusion and outcomes. Results: Of 2528 consecutive patients enrolled from 143 hospitals in the original study, 666 (26.3%) received RBC transfusion (mean age 73.3 ± 16 years, 49% female, initial mean haemoglobin 90 ± 24 g/L, 2.3% had haemodynamic instability). The rebleeding rate in transfused patients was 42.3%. After adjusting for potential confounders, there was no difference between liberal and restrictive RBC transfusion strategies for the odds of rebleeding (OR 0.89, 95% CI 0.6‐1.22), in‐hospital mortality (OR 0.54, 95% CI 0.3‐1.1) or of achieving the composite outcome (OR 0.72, 95% CI 0.5‐1.1). Conclusion: Although these results could be due to residual confounding, they provide an important foundation for the design of randomised trials to evaluate transfusion strategies for LGIB. Abstract : LINKED CONTENT This article is linked to Taha and Kherad and Jairath papers. To view these articles visit, https://doi.org/10.1111/apt.15172 and https://doi.org/10.1111/apt.15189 .